MSC 2021 Virtual E-Abstract: Oral Presentation–Non-Clinical - Stroke Conference, Malaysian (Journal Of Cardiovascular, Neurovascular & Stroke, 2021)
1. A Cluster-Randomised Controlled Trial Evaluating The Effectiveness Of Stroke Riskometer In Improving Stroke Risk Probability In Adults: A Preliminary Analysis. 2. Ph-Weighted Amide Proton Transfer Magnetic Resonance Imaging (APT MRI) Better Delineates The Acidotic Ischemic Penumbra.